STUDI PENYEBARAN SEDIMEN TERSUSPENSI DI PERAIRAN LAUT PAYA KUNDUR PROVINSI KEPULAUAN RIAU - Robileo Agus; Rifardi '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from September-October 2016 at Paya Kundur marine waters, Karimun Regency of Riau Islands Province. Samples were analyzed in the laboratory of Marine Chemistry, Marine Science Department, Faculty of Marine and Fisheries University of Riau. This study aims to determine the vertical profiles of suspended sediment in the marine environment Paya Kundur. This study used survey method, which consists of nine sampling points. Water samples were taken vertically, consists of three levels, namely surface waters, middle (columns), and bottom waters with a distance of ± 6 m. Vertically (surface, middle and bottom) of the distribution of suspended sediment influenced by tidal currents, the location and tin mining activities in bottom waters. The distribution pattern of suspended sediments at ebb tide and flood tide has the highest content at the bottom. The highest content of suspended sediment distribution dominated in the tin mining area to the west of Kundur. Based on quality standart for marine organisme and TSS for fisheries, it can be concluded that waters fertility of Paya Kundur has passed the quality standard and its not suitable for fisheries activities.Keywords: Suspended Sediments, Marine Waters Paya Kundur